Crushing behavior of a thin-walled circular tube with internal gradient grooves fabricated by SLM 3D printing. (February 2017) - Yang, Zhe; Yu, Yangyang; Wei, Yanpeng; Huang, Chenguang
Abstract: Selective laser melting (SLM) is a mature method in the fabrication of structures bearing static loading and small strains; however, structures experiencing large deformation under impact loading remains an issue. In this paper, the author fabricates a 316L stainless steel thin-walled circular tube with preset internal circumferential rectangular groove defects using the SLM method. MTS compression and Split Hopkinson Pressure Bar tests are performed to judge the material behavior of SLM printed 316L stainless steel, and Johnson-Cook constitutive model parameters are fitted from the results. The crushing behavior of the SLM printed tube is studied experimentally and numerically via the drop hammer test and the finite element analysis. There are two stages of the crushing process of the tube as the results show: the buckling stage and the splitting stage. The internal grooves have effects on controlling the initial buckling position and fracture position during the buckling stage. The double buckling-splitting crushing mode in one simple structure, provides a new energy absorption approach for engineering application. Highlights: A steel thin-walled circular tube with internal grooves is fabricated through SLM method. The crushing behavior of the printed tube is studied experimentally and numerically. The tube experiences buckling stage and splitting stage during the process. The internal grooves control the initial buckling position and fracture position.